Teachers' perceptions of well-being from a psychological perspective - Dida Nur Azizah (Journal of Teacher Well-being, 2025)
This study aims to describe primary school teachers' perceptions of well-being from a psychological perspective, as well as the factors that influence it. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews with three teachers from a public primary school in Lamongan Regency. Data were analysed using thematic analysis based on Carol Ryff's psychological well-being theory, which consists of six dimensions: self-acceptance, positive relationships with others, autonomy, environmental mastery, life purpose, and personal growth. The results of the study indicate that teachers have positive perceptions of their psychological well-being, despite facing various challenges in their daily practices. Internal factors such as personality, self-efficacy, and stress management skills influence teachers' perceptions, while external factors include the work environment, administrative workload, and policy support. This study underscores the importance of systemic and personal support in maintaining teachers' well-being to create optimal learning processes.